Factors associated with help-seeking by women facing intimate partner violence in India: findings from National Family Health Survey-5 (2019-2021) - Rakhi Ghoshal; Priti Patil; Isha Sinha; Anita Gadgil; Priyansh Nathani; Nethra Jain; Premkumar Ramasubramani; Nobhojit Roy (BMC, 2024)
Abstract Background Intimate partner violence (IPV) against women has harmful effects on their psychological and physical health. However, help-seeking for IPV is significantly low among women in the Indian context. This study examines the different factors that influence help-seeking behaviour among women in India. It also studies associations of the type of IPV with the source of help. Methods The study analyses data from the fifth round of the National Family Health Survey that was conducted in India (2019-2021). Independent variables were categorized at individual, relationship-household and community levels. The Stata 14.2 software was used to calculate the prevalence ratios and their corresponding 95% confidence intervals. Variables with p-values less than 0.05 were considered statistically significant. Poisson regression helped identify factors associated with help-seeking. Results Results indicate that among 72,320 women aged 18-49 years, 17,765 women ever-faced IPV. Of them, 14.2% of women who faced either physical and/or sexual IPV sought any help. Husband's consumption of alcohol almost doubled the likelihood of help-seeking among women (19.91%), compared to women whose husbands did not drink alcohol (10.19%). Witnessing parental IPV also increased the odds (17.26%) of help-seeking. Women who were not empowered were more likely to seek help (14.11%) compared to women who were empowered (12.56%). The police were the predominant source where women went for formal help (6.94 to 8.43%), followed by doctors (1.84 to 2.71%). Close to 1 in 4 women (22.5%) sought help for sexual IPV, while 14.4% of women sought help for physical IPV. Around 95% of all women who faced IPV sought informal help, with 3 in 5 of them approaching their own families, and 3 in 10 approaching their in-laws or marital families. Conclusions Two significant factors that associate positively with help-seeking by women facing IPV are husbands' alcohol consumption and witnessing parental IPV. Most women preferred informal help from the natal family, while among formal providers, the police were the foremost choice. Programmes and initiatives to build capacities of communities, and of police to respond to women seeking help for IPV, would enable more women to reach out for help.